Modification of nano-silver bioactivity by adsorption on carbon nanotubes and graphene oxide. (15th October 2018) - Hamilton, Raymond F.; Wu, Zheqiong; Thakkar, Megha; Holian, Andrij; Mitra, Somenath
Abstract: Objective: The toxicity of silver nanomaterials in various forms has been extensively evaluated, but the toxicity of silver nanocarbon composites is less well understood. Therefore, silver-carbon nanotube composites (Ag-MWCNT-COOH) and silver-graphene oxide composites (Ag-GO) were synthesized by microwave irradiation and evaluated in two in vitro cell models. Materials/Methods: Toxicity of silver nanosphere (Ag), Ag-MWCNT-COOH and Ag-GO were analyzed by MTS assay and LDH assay in primary C57BL/6 murine alveolar macrophages and human THP-1 cells. Activation of NLRP3 inflammasome by particle variants in these models was done by proxy using LPS co-culture and IL-1β release. Results: The results depended on the model, as the amount of Ag on the modified carbon resulted in slightly increased toxicity for the murine cells, but did not appear to affect toxicity in the human cell model. IL-1β release from carbon particle-exposures was decreased by the presence of Ag in both cell models. Suspensions of Ag-MWCNT-COOH, Ag-GO and Ag in artificial lysosomal fluid were prepared and ICP-MS was used to detect Ag ions concentration in three silver suspension/solutions. The amount of Ag ions released from Ag-MWCNT-COOH and Ag-GO were similar, which were both lower than that of Ag nanospheres. Conclusions: The results suggest the bioactivity of silver composites may be related to the amount of Ag ions released, which can be dependent on the cell model under investigation.